2020
DOI: 10.3389/fonc.2020.00793
|View full text |Cite
|
Sign up to set email alerts
|

Oral Chemotherapy for Treatment of Lung Cancer

Abstract: The global COVID-19 pandemic has disrupted healthcare delivery, particularly for patients with advanced lung cancer. While certain aspects of care can be safely omitted or delayed, systemic therapy plays an important role in survival and quality of life for patients with advanced lung cancer; limiting access to systemic therapy will compromise cancer-related outcomes. This can be at odds with strategies to mitigate risk of COVID-19 exposure, which include reducing hospital and clinic visits. One important stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 58 publications
0
9
0
Order By: Relevance
“…More so, oral administration of targeted therapies for the treatment of some types of cancer such as lung cancer may be an appealing alternative in the current crisis, allowing patients to receive their full therapy while lowering hospital visits and minimizing exposure ( Jonna et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…More so, oral administration of targeted therapies for the treatment of some types of cancer such as lung cancer may be an appealing alternative in the current crisis, allowing patients to receive their full therapy while lowering hospital visits and minimizing exposure ( Jonna et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Discussions already occurring among these shareholders should be accelerated [15]. • Reduce infusion-based treatment in favor of oral therapy where possible [16].…”
Section: We Must Take Steps Now To Avoid a Substantial Increase In Dementioning
confidence: 99%
“…Discussions already occurring among these shareholders should be accelerated [ 15 ]. Reduce infusion-based treatment in favor of oral therapy where possible [ 16 ]. Restart clinical trials that have been halted or deferred due to shifts in funding.…”
Section: Challenges and Early Solutions During The Pandemicmentioning
confidence: 99%
“…It is a potent chemotherapeutic drug for treating breast and non-small cell lung cancer ( 11-13 ). Although oral administration was approved for the clinical application of vinorelbine in 2006 due to convenience and the low risk of venous thrombosis, intravenous infusion exhibits higher efficacy ( 14 ). For example, the results of a phase II study demonstrated that patients with non-small cell lung cancer treated with oral vinorelbine exhibited good tolerance, but displayed limited overall survival time compared with those treated with intravenous vinorelbine ( 15 ).…”
Section: Introductionmentioning
confidence: 99%